Actinodaphne Lawsonii Gamble & apollonias Arnotii Nees (lauraceae) - a New Report to the State of Karnataka - Udayan, P. S.; Robi, A. J. (Indian Forester, 2012)
Botanical survey conducted in the Coorg district resulted in the collection of two Lauraceae species that are new distribution record to Karnataka state. Among them Actinodaphne lawsonii, is an endemic, vulnerable species collected from Talacuvery, after eighty-five years other than the Type collection.